Flexible Beam Manipulations by Reconfigurable Intelligent Surface With Independent Control of Amplitude and Phase - Liang, Jing Cheng; Zhang, Lei; Cheng, Zhang Wen; Zhang, Peng; Cui, Tie Jun (Frontiers in Materials, 2022)
Reconfigurable intelligent surfaces (RISs) have attracted extensive attention in recent years due to their strong ability to improve and customize electromagnetic wave propagation channels in wireless communications. In this article, we propose a design procedure for an RIS and its programmable element, whose reflection phase and amplitude can be jointly controlled by adjusting the states of the varactor and PIN-diode. In addition, by introducing metallic vias in the RIS element, the programmable element can maintain the stable reflection amplitude and phase responses under the illumination of transverse magnetic (TM) wave with the incident angle of 0–60°. In order to verify the beam steering performance of the RIS, theoretical calculations and full-wave simulations of single beam and dual beams are carried out according to the addition theorem of the complex reflection coefficient. The amplitude- and phase-coding patterns on the RIS array are well designed so that the deflection angles and power intensities of the scattered beams can be manipulated independently.